Application Of Legal Maxims In Contract Law: Pacta Sunt Servanda And Islamic Rules On Promises - Muhammad Husni Abdulah Pakarti; Ija Suntana; Ramdani Wahyu Sururie; Lexy Fatharany Kurniawan; Nik Salida Suhaila Nik Saleh (Universitas Negeri Semarang, 2025)
In the practice of contract law, the fulfillment of promises and compliance with agreements are fundamental aspects to ensure justice and legal certainty. The principle of pacta sunt servanda which emphasizes the obligation to honor agreements has relevance to Islamic rules which also require the fulfillment of promises. This research uses normative legal research methods with a comparative juridical approach. Primary data sources are obtained from laws, government regulations, court decisions, and other relevant legal documents. While secondary data is obtained from books, journals, scientific articles, and other literature that discusses the principle of pacta sunt servanda, Islamic rules on promises, and contract law. Data collection techniques use literature study and document analysis, while data analysis techniques use qualitative analysis using the inductive method, and comparative analysis to compare the principle of pacta sunt servanda with Islamic rules of promise. The findings show that pacta sunt servanda and Islamic rules of promise have similarities in emphasizing the importance of commitment to the contract. However, there are differences in the application of these two legal systems, especially regarding exceptions and certain conditions such as force majeure and the principle of benefit in Islam. The principle of pacta sunt servanda and the Islamic rule of promise can complement each other in the practice of contract law, especially in the context of countries that apply legal pluralism. The application of these two principles encourages trust and stability in business transactions. This research recommends strengthening the legal framework that accommodates elements of contract compliance while taking into account aspects of substantive justice and relevant special conditions.